Endocannabinoid System Components as Potential Biomarkers in Psychiatry - Navarrete, Francisco; García-Gutiérrez, María Salud; Jurado-Barba, Rosa; Rubio, Gabriel; Gasparyan, Ani; Austrich-Olivares, Amaya; Manzanares, Jorge (Frontiers in Psychiatry, 2020)
The high heterogeneity of psychiatric disorders, leads to a lack of diagnostic precision. Therefore, the search of biomarkers is a fundamental aspect in psychiatry to reach a more personalized medicine. The endocannabinoid system (ECS) has gained increasing interest due to its involvement in many different functional processes in the brain, including the regulation of emotions, motivation and cognition. This article reviews the role of the main components of the ECS as biomarkers in certain psychiatric disorders. Studies carried out in rodents evaluating the effects of pharmacological and genetic manipulation of cannabinoid receptors or endocannabinoids (eCBs) degrading enzymes. Likewise, the ECS-related alterations occurring at the molecular level in animal models reproducing some behavioral and/or neuropathological aspects of psychiatric disorders were reviewed. Clinical studies evaluating gene or protein alterations in post-mortem brain tissue or in vivo blood, plasma and cerebrospinal fluid (CSF) samples were analyzed. Furthermore, the results from neuroimaging studies using positron emission tomography (PET) or functional magnetic resonance (fMRI) were included. This review shows the close involvement of cannabinoid receptor 1 (CB1r) in stress regulation and the development of mood disorders (anxiety, depression, bipolar disorder (BD)), in post-traumatic stress disorder (PTSD), as well as in the etiopathogenesis of schizophrenia, attention deficit hyperactivity disorder (ADHD) or eating disorders (i.e. anorexia and bulimia nervosa). On the other hand, recent results regarding the potential therapeutic action of the endocannabinoid tone manipulation by inhibition of eCBs degrading enzymes, as well as by the modulation of cannabinoid receptor 2 (CB2r) activity on anxiolytic, antidepressive or antipsychotic associated effects were included. Further clinical research studies are needed, however, current evidence suggests that the components of the ECS may become promising biomarkers in psychiatry to improve, at least in part, the diagnosis and pharmacological treatment of psychiatric disorders.